Comparison of antigen and two molecular methods for the detection of Clostridium difficile toxins. (January 2013) - Ylisiurua, Pirkko; Koskela, Markku; Vainio, Olli; Tuokko, Hanna
Abstract Background: Clostridium difficile (CD) is considered an important cause of diarrhoea associated with the antimicrobial treatment of infections. The pathogenicity of CD is due to toxins A and B, produced by toxigenic CD strains. Methods: We evaluated 3 methods for detecting CD toxins: the RIDASCREEN® enzyme immunoassay (EIA) (R-Biopharm) – one detecting toxins directly in the stool specimens and another detecting toxins from isolated CD strains – and 2 molecular methods, the illumigene™ loop-mediated isothermal amplification (LAMP) assay (Meridian) and RIDA®GENE polymerase chain reaction (PCR) assay (R-Biopharm), as direct identification methods from stool specimens. Toxigenic culture (TC) was used as the reference method. Results: Altogether 884 stool samples were analyzed, of which 253 (29%) were positive by TC. Six hundred and seventy-two specimens were tested by RIDASCREEN EIA, 430 were tested with the illumigene LAMP assay, and 212 were tested with the RIDA GENE PCR assay. CD toxin A and B antigen tests by EIA were very insensitive, both directly from stool specimens (2 series; 57–61%) and in isolated CD strains (53%); consequently the negative predictive value remained low (84–93% and 91%, respectively). Specificity, however, was very good at 98–100%. The 2 molecular methods detected CD toxin genes excellently and equally, resulting in sensitivities, specificities, and positive and negative predictive values of 98%, 100%, 100%, and 98%, respectively. Conclusions: Both molecular assays were easy to use, rapid, sensitive, and specific for the detection of toxigenic CD strains.